Optimization and Evaluation of the PEDF System Configuration Based on Planning and Operating Dual-Layer Model - Tianhe Li; Pei Ye; Haiyang Wang; Weiyu Liu; Xinyue Huang; Ji Ke (Applied Sciences)
The photovoltaic, energy storage, direct current, and flexibility (PEDF) system represents a crucial innovation for transforming buildings into low-carbon energy sources. Although it is still in the early stages of scalable demonstration, current research and practice related to PEDF lack comprehensive studies on optimizing and evaluating system capacity configuration across various scenarios. Capacity configuration and energy scheduling are crucial components that are often treated separately, leading to a missing opportunity to leverage the synergy among key interactive devices. To address this issue, this paper proposes an optimization and evaluation framework for the PEDF system that employs a dual-layer model for planning and operating. This framework precisely configures the PEDF topology, load, photovoltaic, energy storage, and critical interactive devices, while integrating economic, environmental, and reliability objectives. The effectiveness of the proposed model has been validated in optimizing capacity configurations for newly built office buildings and existing commercial settings. The results indicate that for new office buildings, schemes that prioritize low-carbon initiatives are more effective than those that focus on reliability and economy. In existing commercial buildings, reliability-focused schemes outperform those that prioritize economy and low carbon, and all three are significantly better than pre-configuration schemes. The proposed framework enhances the theoretical understanding of PEDF system planning and evaluation, thereby promoting broader adoption of sustainable energy technologies.